Physical Internet, Africa’s Transport Infrastructure and Capacity Building - Mayuto, Radjabu; Aïhounhin, Sègbédji Parfait; Abodohoui, Alexis; Chrysostome, Elie (Journal of Comparative International Management)

(untitled) (Management Futures, 2017)
This paper analyzes capacity building in transportation, logistics, and security in Africa. It is one of the first few research studies that reflects the reality of the development of Africa’s infrastructural capacity for transport, based on the notion of the Physical Internet. Grounded on the analysis of the economic, environmental, and social impacts of transport logistics on the continent, the research sheds light on the deficit in infrastructure capacity of African countries. To this end, the study provides a set of recommendations for capacity building across African transport sectors.